Environmental Stress and their relationship to self-rebellion for Preparatory Stage Students (Journal Of Educational and Psychological Researches, 2022)
The Present research aimed at identifying:    1- The level of environmental stress among preparatory students2- The level of self-rebellion  among preparatory students3- The correlation between the two variables of research (environmental stress and self-rebellion) and the extent to which the independent variable contributes to the variable of the middle school students.  The current research has determined the students of the fifth stage of the preparatory stage and all the branches in the departments of education in Baghdad province the morning study for the academic year 2020-2021                Theoretical framework: Current research reviewed theories adopted in building and interpreting the results   In order to carry out the research goals, the researcher did procedures as follows:1-  Building a measure of environmental stress based on the theory  (Hans saley 1956) 2- Building a measure of self-rebellion adopting a theory (J.W.Brehm1966)  The psychometric characteristics were used with the two scales where the apparent honesty of the two scales was extracted, and the discriminatory strength of the paragraphs and the relationship of the paragraph degree to the total grade of the field and for both scales and each individually after applying the two measures to the sample of statistical analysis of (200) students from the stage Preparatory and stability extraction for both measures and individually in ways: half-fragmentation and vakronbach and retesting and the above measures were applied to a sample of preparatory students and reached (200) students during the period from 5 - 29 /1/2021The following results have been reached      1-The results of the research showed that preparatory students suffer from significant environmental stress compared to the hypothetical average of the scale.  2-The results of the research showed that the students of the preparatory school are practicing self-rebellion.               3-The results showed a positive correlation between environmental stress and self-rebellion and a contribution to increasing student self-rebellion. The researcher has made some recommendations and suggestionsThe researcher submitted some recommendations and suggestions